Characterization and property investigation of microcrystalline cellulose (MCC) and carboxymethyl cellulose (CMC) filler on the carrageenan-based biocomposite film - Mohd Aiman, Hamdan; Nur Amalina, Ramli; Nor Amira, Othman; Khairatun Najwa, Mohd Amin; Fatmawati, Adam (Elsevier Ltd, 2020)
Hard capsule has received high demands not only in the pharmaceutical industry but also in food, cosmetics, and personal care applications. Current hard capsule made from gelatin has contributed to the rise of allergy and halal issues. Thus, many researches were looking for alternatives to produce hard capsule from natural and renewable sources such as carrageenan. In this study, carrageenan was incorporated with carboxymethyl cellulose (CMC) and microcrystalline cellulose (MCC) to toughen the carrageenan based biocomposite film and hard capsule. The cellulose filler used was expected to increase the tensile strength and viscosity properties of the carrageenan matrix due to the development of strong hydrogen bonding between the carrageenan and filler. The crystallinity and functional group properties of CMC and MCC were identified via X-ray diffraction (XRD) and Fourier transforms infrared (FTIR) analysis. Then, the hard capsule was prepared by incorporating carrageenan with isovanillin, PEG, alginic acid at different cellulose filler concentrations. The formulation solution was cast for biocomposite film development and dipped for hard capsule development. The tensile strength of the film was analyzed to study the effect of the cellulose filler on the film produced. Crystallinity result shows that CMC is an amorphous while MCC is a crystal, thus CMC has excellent solubility in water compared to MCC. Moreover, film and hard capsule mechanical properties demonstrated that Carra-CMC has the highest tensile strength in comparison to Carra-MCC. Incorporation of CMC in carrageenan biocomposite film shows a significant increment of viscosity up to 50% and the tensile strength up to 37%. The presence of main three functional groups in CMC structure increased the molecular interaction in the carrageenan biocomposite thus improve the film properties. It is predicted that a higher concentration of CMC is required to produce a more stable Carra-CMC biocomposite film and hard capsule.